KAJIAN PERKEMBANGAN WILAYAH DAN PENILAIAN RISIKO LINGKUNGAN DI PERKOTAAN BANJARMASIN - , AHMAD ZAKY MAULANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Urban development has an impact on quality of urban environment. The study titled \"Study of Urban Development and Environmental Risk Assessment in Urban Area of Banjarmasin\" aims to determine the rate of urban development, environmental risk or impact, and the influence of the urban development to environmental risk in Banjarmasin. This study used a descriptive analysis approach, with primary data, QuickBird imagery Banjarmasin, and secondary data, as the basis for analysis of data. Location of the study are in North Banjarmasin District, East Banjarmasin District and South Banjarmasin District, by used block approach as the unit of analysis. Processing data using data standardization with z-score methods, bivariate correlation test, and simple regression tests using SPSS 17 for windows. A total 9 blocks from 17 blocks have a high rate of urban development, there are 4 blocks on North Banjarmasin District, 4 blocks on East Banjarmasin District, and 1 block on South Banjarmasin District. In environmental risk assessment, a total 8 blocks have a high environmental risk, which is 3 blocks on North Banjarmasin District, 3 blocks on East Banjarmasin District, and 2 blocks on South Banjarmasin District. Analysis correlation of indicator urban development rate variables with environmental risk variables showed that building densities has a very strong correlation with the building areas, road intensities and population densities, proved by the correlation value is greater than 0.8. Analysis the influence of the urban development rate to the environmental risk indicate that the urban development provide a very strong influence to the environmental risk, proved by the R value of 0.814. Urban development gives influence of 66.3% against environmental risks. Classification of urban development and environmental risks resulted 4 (four) regions typology, namely region typology I (high level of urban development and high environmental risk), region typology II (high level of urban development and low environmental risk), region typology III (low level of urban development and high environmental risk) and region typology IV (low level of urban development and low environmental risk). A total of 7 blocks located on region typology I, 2 blocks on region typology II, 1 block on region typology III and 7 blocks on region typology IV. Based on the region typology, there are 4 (four) forms recommendation of urban development: Control, Protection, Revitalization/rehabilitation, and Development. Keywords: city, urban development, environmental risk